Hydroclimatic Drivers of Soil Moisture Decline in South-South Nigeria: Implications for Sustainable Agriculture - Idisi , Benjamin; Ogbereyivwe , Oghovese; Ogbevire , Ejovi (Frontiers in Sustainable Science and Technology, 2025)
This study investigates the hydroclimatic drivers of soil moisture decline in South-South Nigeria from 2000 to 2020, emphasizing implications for sustainable agriculture in rain-fed systems. Utilizing satellite-derived datasets including CHIRPS for precipitation, ERA5 for temperature, and SMAP/AMSR-E for soil moisture, integrated with GIS and statistical analyses (Mann-Kendall trends, Sen's slope, cross-wavelet coherence, and correlation), we reveal a consistent warming trend with maximum temperatures peaking at 28.38°C in 2020, erratic precipitation patterns with highs of 7.01 mm/day in 2015, and a ~6% soil moisture reduction (from 0.325 to 0.305 m³/m³). Correlations indicate a weak positive link between soil moisture and precipitation (r=0.124) and a strong inverse relationship with temperature (r=-0.614), highlighting a temperature-driven evapotranspiration as a primary deficit mechanism. Data limitations, such as satellite biases in vegetated tropics (RMSE 0.04–0.06 m³/m³ for SMAP), were addressed through literature-based validation and cross-referencing with regional benchmarks. These trends pose risks to staples like cassava and rice, projecting 10–25% yield losses. Actionable recommendations include adopting drought-resistant cultivars, conservation agriculture for enhanced retention (15–30%), community water harvesting, and satellite-based early-warning systems. This research informs climate-smart policies to bolster food security and ecosystem resilience amid escalating variability in tropical Africa.